The Impact of Worldwide Military Spending Cutson Developing Countries - Symansky, Steven (IMF Working Papers; Working Paper ;, 1993)
This paper investigates the economic impact of a coordinated reduction in military expenditures of 20 percent using a specially modified version of the MULTIMOD world economic model. Simulation results indicate that in developing countries the present value of consumption increases by 46 percent of 1992 GDP, compared to military expenditures cuts, in present value terms, of 33 percent of 1992 GDP. The gains reflect both the release of domestic resources and a positive international economic externality due to enhanced trade and lower world interest rates. Accordingly, the net debtor developing country gains exceed those of industrial countries. Examination of individual developing country economies confirms the significance of the external trade effect on the pattern and level of gains.